In Indonesia, Hope For The Omnibus Law Method As A Solution To Hyper Regulation - Amirullah Amirullah; Tunggul Anshari SN; Ngesti Dwi Prasetyo (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to describe the expectations of the Omnibus Law Method as a solution to regulatory problems in Indonesia. The research method used is a normative juridical approach with statutory and conceptual approaches. Analytical tools based on the SWOT framework are used to examine primary, secondary, and tertiary sources of law. Due to the overwhelming volume of federal and state laws, the government has chosen to implement sweeping